Optimum duration of adjuvant trastuzumab in treatment of human epidermal growth factor receptor-2 positive early breast cancer: protocol for a network meta-analysis of randomised controlled trials. Issue 11 (20th November 2020) - Hu, Qiancheng; Wang, Xin; Chen, Ye; Li, Xiaofen; Luo, Ting; Cao, Dan
Abstract : Introduction: Controversy regarding optimum duration of trastuzumab treatment remains in patients with human epidermal growth factor receptor-2 (HER2) positive early breast cancer. The objective of applying network meta-analysis (NMA) is to integrate existing evidence based on direct and indirect comparisons of efficacy and safety, and then to determine the duration of trastuzumab treatments with the greatest impact on therapeutic outcomes in HER2-positive early breast cancers. Methods and analysis: Electronic searching of trastuzumab treatments for early breast cancer by titles and abstracts will be conducted for the period from inception to 16 June 2019 in PubMed, Cochrane Library, Embase and ClinicalTrils.gov, as well as the annual meetings of San Antonio Breast Cancer Symposium (SABCS), European Society of Medical Oncology (ESMO) and American Society of Clinical Oncology (ASCO) online archives. The outcomes of interest are overall survival, disease-free survival, acceptability, cardiotoxicities and grade 3 to 4 non-haematological toxicities. Two independent reviewers will screen and extract eligible data based on the inclusion and exclusion criteria, and then assess the risk of bias and evidence quality of individual studies using Cochrane Collaboration's tool and Grades of Recommendation, Assessment, Development and Evaluation (GRADE). The heterogeneity, transitivity and inconsistency of NMA will be evaluated. In addition, we will perform subgroup and sensitivity analyses to assess the robustness and reliability of findings in our NMA. Ethics and dissemination: Ethics approval is not required for our NMA. Findings from our NMA will be submitted as peer-reviewed journal manuscripts and international conference reports. Trial registration number: CRD42019139109.